2009
DOI: 10.1007/s00359-009-0496-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular evolution of olfactory neurons and receptors for aliphatic esters across the Drosophila genus

Abstract: Insect olfactory receptor (Or) genes are large, rapidly evolving gene families of considerable interest for evolutionary studies. They determine the responses of sensory neurons which mediate critical behaviours and ecological adaptations. We investigated the evolution across the genus Drosophila of a subfamily of Or genes largely responsible for the perception of ecologically relevant aliphatic esters; products of yeast fermentation and fruits. Odour responses were recorded from eight classes of olfactory rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 36 publications
5
61
1
Order By: Relevance
“…Seven ORNs showed no significant population differences in their response properties ( figure 1a,b). This high level of conservation in five of the seven ORNs is in line with our understanding from D. melanogaster that they function as general detectors of habitat suitability, for instance, as a general yeast detector (ab1A, ab2A, ab7B, pb2B and pb3B [28,38,39]). The receptors of the remaining two ORNs are unknown.…”
Section: (B) Population Differences In Electrophysiological Responsessupporting
confidence: 79%
See 2 more Smart Citations
“…Seven ORNs showed no significant population differences in their response properties ( figure 1a,b). This high level of conservation in five of the seven ORNs is in line with our understanding from D. melanogaster that they function as general detectors of habitat suitability, for instance, as a general yeast detector (ab1A, ab2A, ab7B, pb2B and pb3B [28,38,39]). The receptors of the remaining two ORNs are unknown.…”
Section: (B) Population Differences In Electrophysiological Responsessupporting
confidence: 79%
“…Having established this within D. mojavensis, we used the mean responses of these subtypes in a cluster analysis with recordings of known D. melanogaster subtypes. This reveals that the three large antennal basiconic (ab) subtypes (Dmojab1 -3) were highly similar in their response properties to their D. melanogaster equivalent (figure 1a; electronic supplementary material, figure S2, [9,18,26,28] Other ORNs did not, and these responses fell into two categories: (i) ORNs previously shown to have high variability among drosophilid species [28,35,38,39] or (ii) ORNs in which the corresponding receptor is not bioinformatically predicted to be present in D. mojavensis [35]. The remaining three, DmojabX -Z, could not be unambiguously matched by their responses to known D. melanogaster subtypes.…”
Section: Results (A) Characterization Of the Response Properties Of Dmentioning
confidence: 90%
See 1 more Smart Citation
“…The OR family has been functionally annotated in D. melanogaster (reviewed in ref. 28), and members of subfamily H OR genes in particular (20) are highly conserved and enriched in receptors for aliphatic esters (35), a group of compounds S. flava detected poorly.…”
Section: Resultsmentioning
confidence: 99%
“…Recent comparative studies revealed OSNs with mainly conserved receptive ranges or conserved representation patterns of odorants in the first olfactory neuropil across species, with only little impact of speciesspecific life histories. In these studies, however, only species belonging to the same family [Nymphalidae (Carlsson et al, 2011;Ômura and Honda, 2009)], subfamily [Heliothinae (Rostelien et al, 2005;Stranden et al, 2003); Murinae (Johnson et al, 2009;Soucy et al, 2009)], or genus [Drosophila (de Bruyne et al, 2010;Stensmyr et al, 2003)] were investigated. Remarkable similarities in olfactory coding were also found across the ant Camponotus fellah, the bee Apis mellifera and the rat Rattus norvegicus, i.e.…”
Section: Introductionmentioning
confidence: 99%